2020
DOI: 10.21203/rs.3.rs-60828/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CDK12/13 Inhibition Induces Immunogenic Cell Death and Enhances Anti-PD-1 Anticancer Activity in Breast Cancer

Abstract: Background: The T cell response against different tumors is improved by immunogenic cell death (ICD), indicating a role for ICD in augmenting antitumor immunity elicited by the anti-checkpoint antibody anti-programmed death 1 (anti-PD-1). Methods: The effect of SR-4835 on breast cancer was analyzed by cell proliferation and flow cytometry. Calreticulin translocation and HMGB1 and ATP release were detected by flow cytometry, ELISA and luminescence assay, respectively. Immunogenicity in vitro was analyzed by co-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…54 The top three candidates in our prioritised gene list are IKZF3, CTLA4 and CDK12, which have previously been identified as crucial regulators of T cell activation. 65,68,69 One of the enhancers connected to CTLA4 (chr2:203930706-203942262), was also connected to ICOS and CD28 in the T cell eGRN (Figure 7B). These three genes, all members of the immunoglobulin supergene family, play important distinct as well as synergistic roles in the regulation of T cell responses 66 , and we observed that their expression was significantly upregulated in all subsets of activated T cells (Figure 7C).…”
Section: Prioritisation and Validation Of Egrn Enhancers-gene Pairs P...mentioning
confidence: 99%
“…54 The top three candidates in our prioritised gene list are IKZF3, CTLA4 and CDK12, which have previously been identified as crucial regulators of T cell activation. 65,68,69 One of the enhancers connected to CTLA4 (chr2:203930706-203942262), was also connected to ICOS and CD28 in the T cell eGRN (Figure 7B). These three genes, all members of the immunoglobulin supergene family, play important distinct as well as synergistic roles in the regulation of T cell responses 66 , and we observed that their expression was significantly upregulated in all subsets of activated T cells (Figure 7C).…”
Section: Prioritisation and Validation Of Egrn Enhancers-gene Pairs P...mentioning
confidence: 99%